Postural Communication of Emotion: Perception of Distinct Poses of Five Discrete Emotions - Lopez, Lukas D.; Reschke, Peter J.; Knothe, Jennifer M.; Walle, Eric A. (Frontiers in Psychology, 2017)
Emotion can be communicated through multiple distinct modalities. However, an often-ignored channel of communication is posture. Recent research indicates that bodily posture plays an important role in the perception of emotion. However, research examining postural communication of emotion is limited by the variety of validated emotion poses and unknown cohesion of categorical and dimensional ratings. The present study addressed these limitations. Specifically, we examined individuals’ (1) categorization of emotion postures depicting 5 discrete emotions (joy, sadness, fear, anger, and disgust), (2) categorization of different poses depicting the same discrete emotion, and (3) ratings of valence and arousal for each emotion pose. Findings revealed that participants successfully categorized each posture as the target emotion, including disgust. Moreover, participants accurately identified multiple distinct poses within each emotion category. In addition to the categorical responses, dimensional ratings of valence and arousal revealed interesting overlap and distinctions between and within emotion categories. These findings provide the first evidence of an identifiable posture for disgust and instantiate the principle of equifinality of emotional communication through the inclusion of distinct poses within emotion categories. Additionally, the dimensional ratings corroborated the categorical data and provide further granularity for future researchers to consider in examining how distinct emotion poses are perceived.